The effect of modified atmosphere on the storage life of fresh culinary herbs - de Guzman, C.C.; Reglos, R. A.; Gannaban, S. C. (1996)
The keeping quality of three popular culinary herbs - Vietnamese basil (Ocimum adscendens Willd.), lemongrass (Cymbopogon citratus (DC) Stapf.) and pandan (Pandanus odoratissimus L.f.) - as influenced by modified atmosphere (MA) storage and temperature during storage was investigated.

The limit of saleability (VQR of 5) of the three culinary herbs kept at 10, 23 and 32 C in open condition was attained after 3 to 4 days of storage. Placing the herbs in polyethylene bag (PEB) or immersing the cut stems or leaves in water resulted in a two-fold extension of shelf-life compared to the control. Moisture loss of these herbs was also markedly reduced by storing them in PEB or in water. Storage at low temperature (10 C) slightly increased the storage life of the herbs. The expression of symptoms typical of chilling injury was observed at this temperature in Vietnamese basil leaves but was minimized when the leaves were placed in PEB.
Keywords: Herbs; Cooking (Herbs); Food storage -- Environmental aspects